Intergenerational value transmission, religiosity, and ethical consumption: Evidence from college students in Indonesia - Rahmatina A Kasri; Karina Mariz; Alin Halimatussadiah (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose – With the implementation of Sustainable Development Goals (SDGs), there has been growing attention towards food-wasting behaviors under the public and scientific domain due to its strong economic, environmental, and social consequences. However, educational institutions–which are expected to implement ethical consumption behaviors–still face various challenges to implement it. Hence, the study aims to identify the determinants influencing food-wasting behavior amongst university students in Indonesia.Methodology – The study employed a quantitative research method, in which primary data from 780 students from Universitas Indonesia is analyzed using the logistic regression model. The main variables used are eating disciplines (proxies of intergenerational value variable), religiosity, and several socio-demographic factors.Findings  –  The study found that current eating discipline, desire to educate/discipline future offspring on the habit of finishing food and meal planning significantly influence food-wasting behavior amongst university students. This implies the importance of intergenerational value transmission in influencing ethical consumption behavior. In contrast, despite being a religious country, no significant relationship was found between religiosity and food-wasting behavior. Types of university degrees and gender were also found to significantly influence food-wasting behavior.Practical implications – The findings implied that families and educational institutions should attempt to increase students’ awareness and induce a more positive value transmission towards ethical consumption behavior, including linking food-wasting behaviors to curriculum and religious teaching/practices. Furthermore, given the reciprocal nature of the intergenerational value transmission, higher awareness regarding food waste issues should encourage a more positive attitude and behavior of students and subsequently be used to influence their families, friends, and offspring in the future.Originality – While some studies have examined the connection between religiosity and ethical consumption behavior, few studies have attempted to assess the relationship between religiosity and individual food-wasting behavior at a collegiate level. This study tries to fill the gap in the context of the university in Indonesia.